Understanding the reading process: Insights from a second grade English language learner - Firman Parlindungan; Irfan Rifai; Fadillah Sandy (EnJourMe (English Journal of Merdeka) : Culture, Language, and Teaching of English, 2020)
The objective of this paper is to make a theoretically informed judgement about how a child processes a text in a reading activity. A second-grade English language learner participated as the subject of this study and was observed for five times of one-on-one guided reading condition (30 minutes each). The observation focused on what happened when the child read, how and what changes occurred over time. We also focused on the individual differences and the role of knowledgeable others in helping the child processed the texts. We took notes on observable behaviors in reading processing, including monitoring activities, self-correction behaviors, and problem-solving strategies. The findings suggest some critical arguments, including (1) reading is a problem-solving activity involving multiple knowledge sources, (2) self-correction in reading is as a sign of progress, and (3) reading progress from novice to expert occurs in different path system. DOI: 10.26905/enjourme.v4i2.4036